Isothermal microcalorimetry – A quantitative method to monitor Trypanosoma congolense growth and growth inhibition by trypanocidal drugs in real time. Issue 2 (August 2018) - Gysin, M.; Braissant, O.; Gillingwater, K.; Brun, R.; Mäser, P.; Wenzler, T.
Abstract: Trypanosoma congolense is a protozoan parasite that is transmitted by tsetse flies, causing African Animal Trypanosomiasis, also known as Nagana, in sub-Saharan Africa. Nagana is a fatal disease of livestock that causes severe economic losses. Two drugs are available, diminazene and isometamidium, yet successful treatment is jeopardized by drug resistant T. congolense . Isothermal microcalorimetry is a highly sensitive tool that can be used to study growth of the extracellular T. congolense parasites or to study parasite growth inhibition after the addition of antitrypanosomal drugs. Time of drug action and time to kill can be quantified in a simple way by real time heat flow measurements. We established a robust protocol for the microcalorimetric studies of T. congolense and developed mathematical computations in R to calculate different parameters related to growth and the kinetics of drug action. We demonstrate the feasibility and benefit of the method exemplary with the two standard drugs, diminazene aceturate and isometamidium chloride. The method and the mathematical approach can be translated to study other pathogenic or non-pathogenic cells if they are metabolically active and grow under axenic conditions. Graphical abstract: Image 1 Highlights: Isothermal microcalorimetry enables heat flow measurement of T. congolense in real-time. Heat flow measurements correlate with number of viable cells. Growth and drug-induced growth inhibition can be deducted from heat flow curves. Pharmacodynamic drug action parameters can be computed from heat flow curves. This method is a valuable tool in the drug discovery process against T. congolense.